128Xe: Test for E(5) Symmetry through DDCM and GOSIA Analysis - Konstantinopoulos, T.; et al., ... (HNPS Advances in Nuclear Physics, 2019)
Lifetime measurements in 128Xe have been undertaken at the JYFL accelerator facility using the novel Coulex-plunger in inverse kinematics technique [1], [2]. Excited states in 128Xe were populated by the natFe(128Xe, 128Xe*) reaction at E(128Xe)=525 MeV and the subsequent de-excitations were detected in the JUROGAM γ-ray array. Two independent analyses of the data were performed. Firstly the Differential Decay Curve Method (DDCM) [3] was applied to determine lifetimes of the excited states. Secondly, matrix elements and their corresponding B(E2) values, were extracted using the computer code GOSIA [4]. The results are presented and compared with the adopted values. Also, B(E2) values obtained from this work are compared to the values predicted by the E(5) critical-point symmetry, since 128Xe has been proposed as a candidate for E(5) symmetry [5].